ANALISIS YURIDIS INPRES NO. 1 TAHUN 2022 TENTANG PELAKSANAAN PROGRAM JAMINAN KESEHATAN DALAM KEBERLAKUANNYA PENDAFTARAN HAK ATAS TANAH - Arsanti, Wulan; Ratnawati Gultom, Elfrida (UNES Law Review, 2023)
The issuance of Presidential Instruction No. 1 of 2022 concerning Optimizing the Implementation of the Health Insurance Program instructs all Ministries to optimize the JKN program, this also instructs the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency to implement the Circular Letter of the Director General of Land Rights Determination and Registration (Dirjen PHP) No.02/ 153-400/II/2022 which contains the Determination of Rights and Registration of Land, as a form of follow-up to Presidential Instruction No. 1 of 2022, so that every application for registration services for the transfer of land rights or ownership rights to apartment units due to sale and purchase must be accompanied by a photocopy of the health insurance social service provider (BPJS) participant card (active participant in the Health Insurance Program (JKN). Type of research The method used is normative (doctrinal) juridical research. land rights because buying and selling are not by legal principles or norms in general, namely the principle of legal certainty, where Presidential Instruction Number 1 of 2022 creates legal uncertainty and is only a policy regulation (beleidsregel/pseudo wetgeving) and is optional or (aanvullendrecht).